Use of vasopressin vs epinephrine to reduce haemorrhage during myomectomy: a randomized controlled trial. (December 2015) - Song, T.; Kim, M.K.; Kim, M.-L.; Jung, Y.W.; Yun, B.S.; Seong, S.J.
Abstract: Objective: To compare the effectiveness and safety of vasopressin with epinephrine for reducing blood loss during laparoscopic myomectomy. Study design: Sixty patients undergoing laparoscopic myomectomy were allocated at random to receive either dilute vasopressin or epinephrine into the serosal and/or overlying myometrium, and just around the myoma. The surgeon was blinded to the group allocation. Blood loss, duration of surgery, degree of surgical difficulty, postoperative pain scores and complications were compared. Results: Patient characteristics (e.g. age, body mass index, demographic data), number of myomas, and location and size of the largest myoma were similar between the two study groups. There were no differences in operative blood loss, operative time, subjective surgical difficulty or postoperative pain between the two groups. Transient and non-serious increases in systolic and diastolic blood pressure and heart rate following intra-operative intramyometrial and/or perimyometrial injection of the vasoconstrictive agent only occurred in the epinephrine group, but the difference between the groups was not significant (13% vs 0%, p  = 0.112). No significant postoperative complications were observed in either group. Conclusions: Injection of dilute epinephrine before laparoscopic myomectomy was comparable to injection of dilute vasopressin in terms of operative blood loss, operative time, subjective surgical difficulty, postoperative pain and complications.